2020
DOI: 10.21203/rs.3.rs-36499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of amyloid-beta and tau in tear fluid of patients with Alzheimer’s disease

Abstract: Background There is growing interest in finding non-invasive alternatives to cerebrospinal fluid (CSF) that could serve as front-line diagnostics for Alzheimer’s disease (AD). In this study, we investigated AD-specific biomarkers in tear fluid.Methods Tear fluid was collected from 25 patients with subjective cognitive decline SCD), 24 patients with mild cognitive impairment (MCI), 11 dementia patients and nine controls. Amyloid-beta peptides (AB38, AB40, AB42), t-tau and p-tau levels in tear fluid were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This result indicates that tears contain 10 times the amount of Aβ peptide in blood. Gijs et al reported that their result in the case of healthy controls also showed Aβ in tears, due to the different tear collection methods and the subjects’ average age. We did not test the same concentration.…”
Section: Resultsmentioning
confidence: 96%
“…This result indicates that tears contain 10 times the amount of Aβ peptide in blood. Gijs et al reported that their result in the case of healthy controls also showed Aβ in tears, due to the different tear collection methods and the subjects’ average age. We did not test the same concentration.…”
Section: Resultsmentioning
confidence: 96%
“…Likewise, CSF biomarkers were measured in tear samples to assess a new non-invasive tool to predict and detect AD. Specifically, three Aβ peptides (Aβ38, Aβ40, and Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) were analyzed in patients diagnosed with clinical dementia, MCI, and subjective cognitive decline (SCD), as well as in a control group [ 129 ] ( Table 1 ). Interestingly, the concentrations of all peptides were higher in tear samples of all patient groups compared to healthy subjects; however, non-statistical differences were obtained.…”
Section: Ocular Alterations Related To Admentioning
confidence: 99%
“…Interestingly, the concentrations of all peptides were higher in tear samples of all patient groups compared to healthy subjects; however, non-statistical differences were obtained. In addition, t-tau levels were significantly higher in dementia, MCI, and SCD compared to the control group [ 129 ]. Importantly, p-tau was also detected in all patient groups but not in control subjects.…”
Section: Ocular Alterations Related To Admentioning
confidence: 99%
See 1 more Smart Citation